If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5n + 3n = 4n + -5n Combine like terms: -5n + 3n = -2n -2n = 4n + -5n Combine like terms: 4n + -5n = -1n -2n = -1n Solving -2n = -1n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add 'n' to each side of the equation. -2n + n = -1n + n Combine like terms: -2n + n = -1n -1n = -1n + n Combine like terms: -1n + n = 0 -1n = 0 Divide each side by '-1'. n = 0 Simplifying n = 0
| x^2=x+25 | | y=17x+544 | | 7x+10=27 | | 6w+5-5w=8-3 | | 6=2x+6(x+5) | | -112=7j | | -4(x+2)=6x+10x+2 | | (x+5)2-(x+5)(x-5)= | | -5r-2r=-15-8r+3+7 | | 4x-5=4x+9 | | -3w+8(w-4)=-2 | | 7-2b=19 | | 75=10x-5 | | 1+b=-18-4 | | 27+3x=111 | | -13m+7m=19-73 | | 5x+11=12x-10 | | 10x-2-6x=3y-2+y | | 3x+15+9x+21=180 | | -11x-20=10+40 | | 6y+12=3t+14 | | 6(v+4)-4v=4 | | 14s+2.00=20s+1.50 | | 15Z-32=13 | | -9=-5+t | | x=3+2i | | 14s+2=20s+150 | | -9=5+t | | 8x-7=6x+23 | | 2(x-3)=2*x | | 2w-6w=56 | | 5x+6+6x+5=50 |